PERLINDUNGAN TERHADAP ASYLUM SEEKER DILUAR WILAYAH SUATU NEGARA KAITANNYA DENGAN TANGGUNG JAWAB NEGARA MENURUT PASAL 33 AYAT (1) KONVENSI 1951 TENTANG STATUS PENGUNGSI STUDI KASUS AUSTRALIA-INDONESIA - Martedjo, Wagiman; Ananta, Riyan; Melati, Sri Gambir; Rajaguguk, Parluhutan (Fakultas Hukum, 2023)
This research aims to find out: first, whether the actions of Australia fought off and returning asylum seekers outside its territory by pushing it into the territory of Indonesia in accordance with article 33, paragraph (1) of the 1951 Convention on the Status of Refugees? Second, whether the entry into force of the Convention, 1951 and the 1967 Protocol on the Status of Refugees can be legally binding with respect to Indonesia as the country is not a party? The research method used is the juridical normative research methods using secondary data legal materials that consist of primary legal materials and legal materials tertiary secondary. A summary of research results as follows: first, that the treatment of Australia is a form of international offences because contrary to Article 33 of the 1951 Convention Refugee Status. Second, that Indonesia attached Convention 1951 and the 1967 Protocol on the Status of refugees.